The impact of bidirectional emotional support on social isolation in older adults: the mediating role of depression and the moderating role of activities of daily living - Yang, Chunhui; Shi, Zhongsu; Song, Junnan; Liu, Huan; Zheng, Lin; Liu, Annuo (Frontiers in Public Health, 2025)
ObjectiveTo investigate the impact of bidirectional emotional support on social isolation among community-dwelling older adults and the underlying mechanisms of this effect.MethodsIn this study, 1,136 community-dwelling older adults were recruited from Hefei City, China in 2022 using a stratified random sampling method. Data were collected using the General Information Questionnaire, the Intergenerational Support Scale, the Social Network Scale, the Geriatric Depression Scale, and the Activities of Daily Living (ADL) Scale. Correlation analyses, as well as mediation and moderation tests, were conducted to examine the relationship between bidirectional emotional support and social isolation.ResultsBidirectional emotional support significantly predicted (β = 0.213, P < 0.01) social isolation in older adults. Depression partially mediated the relationship between bidirectional emotional support and social isolation, with an indirect effect of 0.066, representing 23.66% of the total effect. ADL substantially moderated (β = 0.068, P < 0.01) the impact of bidirectional emotional support on depression.ConclusionBidirectional emotional support is a key modifiable factor influencing social isolation. Its impact is partly mediated by depressive symptoms and is also moderated by ADL. These findings suggest that “bidirectional emotional support” should be incorporated into the National Essential Public Health Services Program. Depression screening should be conducted during primary care visits, and emotional support should be provided in a tiered manner based on activities of daily living capabilities to alleviate social isolation among older adults.